Synthesis of drug intermediates in carbon dioxide - Clark, Peter David (2007)
The application of supercritical C0₂(scC0₂) as a solvent for the synthesis of fine and bulk chemicals has been well documented; however its application as a solvent for the synthesis of pharmaceuticals is yet to be exploited fully. To address this issue, two synthetically important reactions have been investigated in scC0₂; chemoselective N-debenzylation and diastereoselective hydrogenation.